Postmenopausal Motherhood Reloaded: Advanced Age and In Vitro Derived Gametes. (7th March 2015) - Cutas, Daniela; Smajdor, Anna
Abstract : In this paper we look at the implications of an emerging technology for the case in favor of, or against, postmenopausal motherhood. Technologies such as in vitro derived gametes (sperm and eggs derived from nonreproductive cells) have the potential to influence the ways in which reproductive medicine is practiced, and are already bringing new dimensions to debates in this area. We explain what in vitro derived gametes are and how their development may impact on the case of postmenopausal motherhood. We briefly review some of the concerns that postmenopausal motherhood has raised—and the implications that the successful development, and use in reproduction, of artificial gametes might have for such concerns. The concerns addressed include arguments from nature, risks and efficacy, reduced energy of the mother, and maternal life expectancy. We also consider whether the use of in vitro derived gametes to facilitate postmenopausal motherhood would contribute to reinforcing a narrow, geneticized account of reproduction and a pro‐reproductive culture that encourages women to produce genetically related offspring at all costs.